Prisoner Interpretations and Expectations for the Ethical Governance of HMIP Survey Data. Issue 3 (1st September 2020) - Quinn, Anthony; Shaw, Catherine; Hardwick, Nick; Meek, Rosie; Moore, Chloe; Ranns, Helen; Sahni, Shannon
Abstract : The value of and the need for rich data for criminal justice research is increasingly apparent, especially following recent restrictions on primary data collection due to COVID-19. Whilst the benefits of using administrative data for research are well established, less understood are the perspectives of data contributors and their expectations for the ethical governance and use of these data. This study describes the findings from a preliminary study comprising four focus groups with a total of seventeen adult males serving sentences in a Category A prison in England. Participants were asked to offer opinions about the possibility of making survey data collected from them as part of the prison inspection process more widely accessible, beyond the organizational priorities for which it was initially collected. Generally, participants were content for survey data to be shared with recipients who intended to use the data to bring about change within prisons; this aligns with the purpose for data collection. Participants were opposed to data being made accessible to recipients who might produce spurious findings. We discuss implications for the future accessibility of a vast wealth of prisoner survey data in England and Wales and highlight the importance of consultation with incarcerated persons on this subject.